PROFILE OF STUDENTS’ CONCEPTUAL CHANGE ABILITIES INMOTION MATERIAL - Ardiansyah; Lilies N. Tangge; Afadil (International Journal of Teaching and Learning, 2024)
This research aims to describe students' conceptual change abilities. This research uses a descriptive method. The research subjects were 22 students at MA Alkhairaat Biromaru class X MIPA. The research instrument uses 5 concept questions about relative motion, distance and displacement, GLB, GLBB and GJB with 1 question each. The N-Gain test carried out on the concept change test showed that there were differences in resultspretest andPosttest based on test N-Gain is 65.23% in the medium category. Conceptual Change Capability of the pra concepts constructed by students from the experience gained, most of which are not in accordance with scientific concepts. From the 5 items regarding concepts about movement, it can be seen that the students' pretest results (pre-concept abilities) are still very low. To carry out the process of changing students' preconcepts, it is necessary to use an approach or learning model that involves the process of Assimilation and Accommodation in the learning process, because changing students' pra concepts requires a cognitive conflict that is able to convince students that their initial knowledge (pra concepts) has been constructed into knowledge. science can be replaced with correct and appropriate concepts.